Vernacular Wooden Architecture in the City of Puntarenas: First Steps Towards Its Recognition - Kenia García-Baltodano; David Porras-Alfaro (Buildings)
In Puntarenas City, a historic and tourist port of Costa Rica, several vernacular buildings constructed in wood can be observed. Despite the prevalence of this architectural type in the area, there is an absence of comprehensive studies aimed at documenting this significant heritage. This article seeks to identify the vernacular architecture in this city through the architectural characterization, quantification, and geolocation of existing buildings, as well as the preliminary recognition of the state of conservation of the group of buildings. The methodological process proposed a four-stage approach. The initial stage involved an examination of documentary sources to verify existing information and obtain a preliminary profile of architectural characteristics. A participatory workshop with the community enabled the validation of this profile. The second stage comprised fieldwork, which yielded a starting list of properties. In the third stage, a detailed examination of the listed properties enabled the verification of the profile of characteristics, the delimitation of the architectural typologies, and the selection of buildings that did not fulfill the preliminary profile or possessed significant modifications that affected their architectural legibility. The fourth stage comprised the development of an inventory of vernacular architecture buildings and the systematic data transference to a Geographic Information System. This study mainly obtained the following results: an initial list of 172 wooden buildings in Puntarenas City and a geolocated inventory of 75 vernacular wooden architecture buildings that exhibit considerable architectural legibility. Moreover, identifying the uses and architectural features of the inventoried buildings permitted their categorization into ten distinct typologies.